Stake and stage: judicial burning and Elizabethan theatre, 1587-1592 - Yardy, D (2015)
This thesis is the first sustained analysis of the relationship between Elizabethan theatre and the judicial practice of burning at the stake. Focusing on a five-year window of theatrical output (1587-1592), it argues that polemical literary presentations of burning are the key to understanding the stage's negotiation of this most particular form of judicial violence. Unlike other forms of penal violence, burning at the stake was not staged, and only fourteen incidences of the punishment are recorded in Elizabethan England. Its strong literary presence in Protestant historiography is therefore central to this study. Part I explores the tragic and overtly theatrical rhetoric that the widely available Acts and Monuments built around the burning of heretics in the reformation, and argues that the narrative of this drama of injustice intervened in the development of judicial semiotics over the late-sixteenth century. By the time that Tamburlaine was first performed, burning at the stake was a pressing polemical issue, and it haunts early commercial theatre. Elizabethan historiography of the stake was deeply influential in Elizabethan theatre. In Part II, I argue that Marlovian fire spectacles evoke tableaux from the Acts and Monuments to encourage partisan spectatorship, informed by the rhetoric of martyrdom. Dido's self-immolation courts this rhetoric by dismissing the sword from her death, while Tamburlaine’s book burning is condemned through its emphatically papist undertones. These plays court the stake through spectacles utilizing its rhetoric. In Part III, I show that characters historically destined to face the stake required thorough criminalization to justify their sentence. Alice Arden is distinguished from female martyrs celebrated for their domestic defiance, while Jeanne d'Arc's historical heresy is forcefully rewritten as witchcraft and whoredom to condemn 1 Henry VI's Joan la Pucelle. Both women are punished offstage, and the plays focus instead on the necessary task of justifying the sentence of burning. Though rare in practice, burning at the stake was a polemical issue in Elizabethan England. Despite the stake’s lack of imitation in the theatre, I argue that widely available Protestant historiography—propaganda at the heart of debates about burning and religious violence—affected both how plays were written, and how they could be viewed.